DISCOURSE KONSEP AGING DALAM MIRACLE MAGZ - Poppy Febriana (Kanal: Jurnal Ilmu Komunikasi, 2012)
Many anti aging advertisements depict women’s fear of growing old.Being old is always linked with weakness, helplessnes or other drawbacks. These makes people always try to look young. This research aims to look at how the media (in this case Miracle Magz) produce and reproduce the knowledge/information about aging and look at how the anti aging problems faced bywomen. The purpose was to find out how the media acred (in this case Miracle Magz) in producing and reproducing knowledge/ information about aging and to analyze the anti aging values which articulated in the media discourse as the answer towards the aging problem faced by women. The result showed that Miracle Magz build new knowledge/ information and change the readers paradigm about aging. When their feelings were hurt, their ego crushed, then they were given the simple solution to get out of any problems, without letting The Miracle Magz readers out of consumptive lifestyle. Each part of their body was made as if they were pieces of puzzles that could be separated from each other and each must be perfected.